Analisis Yuridis Peristiwa Kebocoran Data Daftar Pemilih Tetap Dalam Penyelenggaraan Pemilihan Umum Tahun 2024 - Michael Michael; Rasji Rasji (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
Recently, the public was shocked by the news of a data breach involving 240 million entries from the permanent voter list. This data was leaked from the official website of the General Elections Commission of the Republic of Indonesia by a hacker using the pseudonym “Jimbo”. The data was sold online on BreachForums for USD 74,000. This incident has raised serious concerns among the public due to its broad potential impact on the confidentiality of citizens' personal information and has prompted new questions regarding the accountability of the General Elections Commission of the Republic of Indonesia as the election organizer. In this research, the researcher employs a normative juridical approach by reviewing secondary data collected through library research and using a case and regulatory approach. Based on the research findings, the protection of personal data by the General Elections Commission of the Republic of Indonesia is not yet optimal, as the regulations held by the General Elections Commission of the Republic of Indonesia are only internally applicable and do not have the legal strength equivalent to laws. These the General Elections Commission of the Republic of Indonesia regulations are only applicable to regional head elections and general elections. Furthermore, it is necessary to enhance literacy on the importance of data so that all members of the General Elections Commission of the Republic of Indonesia understand the mechanisms of data processing, inputting, and processing. The General Elections Commission of the Republic of Indonesia members must determine the types of data that can be published and those that should not be exposed to the public, thus enabling the General Elections Commission of the Republic of Indonesia to fulfill its obligations to protect and be accountable for the data obtained from the public.